Does foreign aid reduce income inequality in developing countries? - Bon Van Nguyen; Tuong My Cat Vu; Thao Thi Thanh Nguyen; Nhi Buu Duong; Khoa Ngoc Anh Pham; Toa Trieu Kim Le (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration)
Income inequality has become an increasingly pressing concern within developing economies. Foreign aid, a crucial source of financial assistance, plays a significant role in bridging the wealth gap in these nations. This paper delves into the research question of whether foreign aid effectively mitigates income inequality in developing countries. It does so by examining a dataset spanning from 2002 to 2022, encompassing 29 developing economies, and employs the difference GMM Arellano-Bond estimators. The results of this analysis demonstrate that foreign aid has a tangible and positive impact on reducing income inequality within these nations. In addition, economic growth plays a vital role in diminishing income inequality. On the flip side, trade openness and institutional quality exacerbate income inequality. These findings yield valuable policy insights for governments in developing countries, emphasizing the importance of utilizing foreign aid effectively as a means to combat income inequality.